Early Modern Mathematical Instruments - Bennett, Jim (The Best Writing on Mathematics 2013, 2014)
For the purpose of reviewing the history of mathematical instruments and the place the subject might command in the history of science, if we take “early modern” to cover the period from the 16th to the 18th century, a first impression may well be one of a change from vigorous development in the 16th century to relatively mundane stability in the 18th. More careful scrutiny suggests that this perception is relative and depends more on our priorities as historians than on the interests of the instrument manufacturers or users. In fact, the role of mathematical instruments and the agenda of